Narodowy Zasób Biblioteczny - doświadczenia dziesięciu lat - Renata Piejko (Biblioteka)
November 24th, 2008 marks the tenth anniversary of the issuing of the regulation defining the National Library Stock Creation and the rules governing its preservation along with the list of libraries to be included in the scheme. The inclusion of a library in the list of participating libraries is a proof of the appreciation of the importance of the collections of a particular library 011 the one hand, but imposes additional tasks related to the preservation and the processing of the resources and the care of its preservation 011 the other. It should be noticed at this juncture that unfortunately no unambiguous definition of the National Library Stock has been provided yet and, likewise there are 110 proper indication of financial resources to be assigned in support of these additional tasks imposed 011 the selected libraries. Things as they are, however, make the scope and the pace of work in individual libraries particularly dependent on their individual capabilities and worked out criteria to be applied.